Mitigation of Forest Fire Disasters Tribe Anak Dalam Merangin Jambi - Wulandari, Diana; Subaryanta, Subaryanta (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
preventing and reducing the number of fatalities and affected populations is a matter that urgently needs attention by the government in managing disaster fire risk in Merangin District. In particular, local governments play a role in reducing the risk of forest fires. Therefore the role of local government is very important to achieve this goal. Jambi Province is an area that is prone to the danger of forest fires with high density, one of which is forest and land fires. This article aims to illustrate the capacity of the local government of Jambi in the context of tackling the disaster of forest land fires. This research method used is a qualitative method with interviews, especially to local governments. The findings show that the capacity of the Jambi Regional Government still needs to be improved. In implementing this, what needs to be improved is the knowledge and skills of local government staff in disaster management of forest land fires, and village level preparedness programs and less detailed disaster maps.